A critique of Chinese diplomatic modernization narratives: reinterpreting shifts in Qing foreign affairs institutions in the early 1860s from the Qing perspective. (10th October 2021) - Hayamaru, Kazumasa
Abstract: Scholars have long read the shifts in late Qing China's institutional framework for diplomatic interactions through a lens derived from the Western European diplomatic paradigm. However, such a methodology fails to accommodate the autochthonous perspective of the Qing bureaucrats who initiated these shifts in the first place. Drawing upon two case studies from the 1860s, the Zongli Yamen and the proposed Superintendent of Trade for the Yangzi, this article attempts to understand the motivations and priorities of the Qing in establishing new frameworks for diplomatic interactions in this period. The article argues that, for the Qing, it was not the establishment and the efficacy of these new institutions that was important. What mattered to them in this period was how these new institutions could eventually be abolished and an older, idealized form of practice reinstated in their place.